A New Natural Antioxidant Mixture Protects against Oxidative and DNA Damage in Endothelial Cell Exposed to Low-Dose Irradiation. (9th August 2017) - Cervelli, T.; Panetta, D.; Navarra, T.; Gadhiri, S.; Salvadori, P.; Galli, A.; Caramella, D.; Basta, G.; Picano, E.; Del Turco, S.
Abstract : Exposure to ionizing radiation during diagnostic procedures increases systemic oxidative stress and predisposes to higher risk of cancer and cardiovascular disease development. Many studies indicated that antioxidants protect against radiation-induced damage and have high efficacy and lack of toxicity in preventing radiation exposure damages. The purpose of this study was to investigate the in vitro protective effect of a new antioxidant mixture, named RiduROS, on oxidative stress generation and DNA double-strand breaks (DSBs) induced by low doses of X-rays in endothelial cells. Human umbilical vein endothelial cells (HUVEC) were treated with RiduROS mixture 24 h before a single exposure to X-rays at an absorbed dose of 0.25 Gy. The production of reactive oxygen species (ROS) was evaluated by fluorescent dye staining and nitric oxide (NO) by the Griess reaction, and DSBs were evaluated as number of γ -H2AX foci. We demonstrated that antioxidant mixture reduced oxidative stress induced by low dose of X-ray irradiation and that RiduROS pretreatment is more effective in protecting against radiation-induced oxidative stress than single antioxidants. Moreover, RiduROS mixture is able to reduce γ -H2AX foci formation after low-dose X-ray exposure. The texted mixture of antioxidants significantly reduced oxidative stress and γ -H2AX foci formation in endothelial cells exposed to low-dose irradiation. These results suggest that RiduROS could have a role as an effective radioprotectant against low-dose damaging effects.